Case Report: Japanese Siblings of Cystic Fibrosis With a Novel Large Heterozygous Deletion in the CFTR Gene - Kawase, Mayumi; Ogawa, Masato; Hoshina, Takayuki; Kojiro, Masumi; Nakakuki, Miyuki; Naruse, Satoru; Ishiguro, Hiroshi; Kusuhara, Koichi (Frontiers in Pediatrics, 2022)
Cystic fibrosis (CF) is a rare disease in the Japanese. The most common CFTR variant in Japanese CF patients is a large heterozygous deletion that can easily avoid detection by standard gene sequencing methods. We herein report a novel large heterozygous deletion in the CFTR gene in Japanese siblings with CF. A genetic analysis was performed in two patients (9-year-old boy and 5-month-old girl) who were clinically diagnosed with CF because of the positive result for the rapid fecal pancreatic elastase antigen test and the elevation of the sweat chloride concentration. In addition to conventional polymerase chain reaction (PCR) and direct sequencing, multiplex ligation-dependent probe amplification (MLPA) was performed to check for a large deletion and duplication of the CFTR gene. Based on MLPA findings, the breakpoint of heterozygous deletion was identified by real-time quantitative PCR followed by the sequence of the amplified junction fragment. In MLPA, the numbers of the fragments corresponding to exons 1, 16, 17a, and 17b and 234 nt and 747 nt upstream from the translation initiation codon of exon 1 in the CFTR gene and exon 3 in the ASZ1 gene were reduced by almost half. The c.2908+1085_3367+260del7201 variant (exon 16-17b deletion) was identified in one allele. The other allele had a large 137,567-bp deletion from g.117,361,112 (ASZ1 3’ flanking region) to g.117,498,678 (CFTR intron 1) on chromosome 7. Since the deletion variant lacked the entire promoter region of CFTR, CFTR mRNA would not be transcribed from the allele, indicating it to be a novel pathogenic variant causing CF. As large mutations are frequently detected in Japanese CF patients, MPLA can be useful when searching for variants.